Representasi Etnisitas Dalam Serial Animasi Adit Dan Sopo Jarwo - Shelvy Awailul Ramadhani; Aliv Fatima Latifah; Restu Ismoyo Aji (Student Scientific Creativity Journal, 2023)
This paper aims to answer the question whether the representations of a number of characters in the animated series Adit dan Sopo Jarwo contain ethnic stereotypes that exist in society. Adit dan Sopo Jarwo animated series depicts a neighborhood in the city of Jakarta by lifting the stories of the daily lives of Indonesian citizens. In it there are many characters with various ethnic backgrounds in Indonesia. Through semiotic analysis, it was revealed that two characters, named Babah Chang and Pak Anas, although in characters are outside the prevailing stereotypes, visually and verbally they still use stereotypes according to the ethnic origin of the two characters.